Demetrius and style: a brief history of the translation of a title - Cairus, Henrique Fortuna; Almeida, Marina Albuquerque de (Revista Archai, 2020)
The modern concept of ‘style’ ”“ from which ‘stylistics’ is derived, a discipline that witnessed the quarrel between Linguistics and Literary studies in the 20th century ”“ has inherited from Ancient Rhetoric its substance (figures and tropes) and was largely used as a direct translation from the Latin concept ‘elocutio’ (especially in Demetrius’ treatise De elocutione [Î ÎµÏá½¶ á¼‘ÏÎ¼Î·Î½ÎµÎ¯Î±Ï‚]) and also as a translation for Greek concepts (usually indirectly), such as á¼‘ÏÎ¼Î·Î½ÎµÎ¯Î±, Î»ÎÎ¾Î¹Ï‚ and Ï†ÏÎ¬ÏƒÎ¹Ï‚. There are still some other concepts that seem intimately connected to ‘style’, for instance ‘ornatum’ and ‘decorum’. Considering that classical references of ‘style’ present themselves essential to write the history of this modern concept, this paper seeks to present a catalog of ancient concepts that have found in ‘style’ (in English and French) their traditional translation, as well as attempting to build a short history of each of these translation paths.